User Perceptions of Current Awareness Services: A Faculty Survey. - Leila Fernandez (Issues in Science and Technology Librarianship)
A survey was sent out to science faculty at York University to determine researchers' use of current awareness services. Responses indicate that faculty use a variety of approaches to keep up to date with their research and that there is overall satisfaction with these services. The implications of their choices are discussed with particular reference to future library services.